AREAS OF APPLICATION PROGRAMMING LANGUAGES PYTHON AND RUBY - Гафияк, Алла; Бородина, Елена; Алёшин, Сергей; Смыслов, Сергей; Сапсай, Евгений (Modern engineering and innovative technologies, 2017)
The purpose of the article is to describe the programming languages Python and Ruby, disclosing their advantages over other programming languages. The content of the article is an overview, while the possibilities are revealed and the areas of application